Partial trisomy 17q and a generalised bone dysplasia in a 12 week fetus. Issue 8 (August 1987) - Robb, A; Forsyth, L; Tolmie, J
Abstract : A fetus, which was spontaneously aborted at 12 weeks' gestation, was found to have a generalised bone dysplasia and an unbalanced karyotype with trisomy for 17q23.1----qter due to a maternal translocation: 46, XX, t(5;17)(p15.3;q23.1)mat.